Editorial: Aerosol deposition in the ocean: drivers and biogeochemical effects - Catarina V. Guerreiro; Jan-Berend W. Stuut; Cécile Guieu; Tim Jickells (Frontiers in Marine Science, 2026)

Climate Benefits of Saltmarsh Restoration Greatly Overstated by Mason et al. (2023) - Phillip Williamson; Robert W. Schlegel; Jean‐Pierre Gattuso; Julian E. Andrews; Tim D. Jickells (Global Change Biology, 2024)

Surface Inorganic Iodine Speciation in the Indian and Southern Oceans From 12°N to 70°S - Rosie Chance; Liselotte Tinel; Amit Sarkar; Alok K. Sinha; Anoop S. Mahajan; Racheal Chacko; P. Sabu; Rajdeep Roy; Tim D. Jickells; David P. Stevens; Martin Wadley; Lucy J. Carpenter (Frontiers in Marine Science, 2020)

Impacts of Global Change on Ocean Dissolved Organic Carbon (DOC) Cycling - Christian Lønborg; Cátia Carreira; Tim Jickells; Xosé Antón Álvarez-Salgado (Frontiers in Marine Science, 2020)

Carbon on the Northwest European Shelf: Contemporary Budget and Future Influences - Oliver Legge; Martin Johnson; Natalie Hicks; Tim Jickells; Markus Diesing; John Aldridge; Julian Andrews; Yuri Artioli; Dorothee C. E. Bakker; Michael T. Burrows; Nealy Carr; Gemma Cripps; et al. (Frontiers in Marine Science, 2020)

Variation in dissolved organic matter (DOM) stoichiometry in U.K. freshwaters: Assessing the influence of land cover and soil C:N ratio on DOM composition - Christopher A. Yates; Penny J. Johnes; Alun T. Owen; Francesca L. Brailsford; Helen C. Glanville; Christopher D. Evans; Miles R. Marshall; David L. Jones; Charlotte E. M. Lloyd; Tim Jickells; Richard P. Evershed (Limnology and Oceanography, 2019)
Dissolved organic matter (DOM) plays an important role in freshwater biogeochemistry. To investigate the influence of catchment character on the quality and quantity of DOM in freshwaters, 45 sampling sites draining subcatchments of contrasting soil type, hydrology, and land cover within one large upland‐dominated and one large lowland‐dominated catchment were sampled over a 1‐yr period. Dominant land cover in each subcatchment included: arable and horticultural, blanket peatland, coniferous woodland, and improved, unimproved, acid, and calcareous grasslands. The composition of the C, N, and P pool was determined as a function of the inorganic nutrient species (NO 3 − , NO 2 − , NH 4 + , and PO 4 3− ) and dissolved organic nutrient (dissolved organic carbon [DOC], dissolved organic nitrogen [DON], and dissolved organic phosphorus [DOP]) concentrations. DOM quality was assessed by calculation of the molar DOC : DON and DOC : DOP ratios and specific ultraviolet absorbance (SUVA 254 ). In catchments with little anthropogenic nutrient inputs, DON and DOP typically composed > 80% of the total dissolved nitrogen (TDN) and total dissolved phosphorus (TDP) concentrations. By contrast, in heavily impacted agricultural catchments DON and DOP typically comprised 5–15% of TDN and 10–25% of TDP concentrations. Significant differences in DOC : DON and DOC : DOP ratios were observed between land cover class with significant correlations observed between both the DOC : DON and DOC : DOP molar ratios and SUVA 254 ( r s = 0.88 and 0.84, respectively). Analysis also demonstrated a significant correlation between soil C : N ratio and instream DOC : DON/DOP ( r s = 0.79 and 0.71, respectively). We infer from this that soil properties, specifically the C : N ratio of the soil organic matter pool, has a significant influence on the composition of DOM in streams draining through these landscapes.

Ship-Based Contributions to Global Ocean, Weather, and Climate Observing Systems - Shawn R. Smith; Gaël Alory; Axel Andersson; William Asher; Alex Baker; David I. Berry; Kyla Drushka; Darin Figurskey; Eric Freeman; Paul Holthus; Tim Jickells; Henry Kleta; et al. (Frontiers in Marine Science, 2019)

Megacities and Large Urban Agglomerations in the Coastal Zone: Interactions Between Atmosphere, Land, and Marine Ecosystems - Roland von Glasow; Tim D. Jickells; Alexander Baklanov; Gregory R. Carmichael; Tom M. Church; Laura Gallardo; Claire Hughes; Maria Kanakidou; Peter S. Liss; Laurence Mee; Robin Raine; Purvaja Ramachandran; et al. (Ambio, 2013)

Seasonal and interannual variation of the phytoplankton and copepod dynamics in Liverpool Bay - Naomi Greenwood; Rodney M. Forster; Veronique Créach; Suzanne J. Painting; Anna Dennis; Stewart J. Cutchey; Tiago Silva; David B. Sivyer; Tim Jickells (Ocean Dynamics, 2012)

Spatial and seasonal changes of dissolved and particulate organic C in the North Sea - Suhaimi Suratman; Keith Weston; Tim Jickells; Liam Fernand (Hydrobiologia, 2009)

Seasonal variability of inorganic and organic nitrogen in the North Sea - Suhaimi Suratman; Tim Jickells; Keith Weston; Liam Fernand (Hydrobiologia, 2008)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)